A population of dermal Langerin+ dendritic cells promote the inflammation in mouse model of atopic dermatitis - Xiao, Chunying; Zhu, Zhenlai; Zhang, Chen; Gao, Jixin; Luo, Yixin; Fang, Hui; Qiao, Hongjiang; Li, Wei; Wang, Gang; Fu, Meng (Frontiers in Immunology, 2022)
Cutaneous dendritic cells (DCs) have been implicated in the pathogenesis of atopic dermatitis (AD). However, the specific role of different subsets of DCs has not been well defined. This study aimed to investigate the contributions of Langerhans cells (LCs), resident dermal Langerin+ DCs (r-Langerin+ dDCs), and newly infiltrated inflammatory dermal Langerin+ DCs (i-Langerin+ dDCs) in an AD mouse model induced by the topical application of MC903. The result showed that depletion of i-Langerin+ dDCs in DTR mice after multiple diphtheria toxin (DT) injection significantly reduced thymic stromal lymphopoietin (TSLP) production in lesions and skin inflammation alleviation. However, depletion of LCs or r-Langerin+ dDCs didn’t resulted in significant changes in skin inflammation of DTA or single DT injection-treated DTR mice compared with the wild-type (WT) mice. DT-treated DTR-WT chimeric mice with the depletion of bone marrow (BM)-derived i-Langerin+ dDCs resulted in markedly decreased skin inflammation than controls, while PBS-treated chimeric mice (DTR-WT) with only the depletion of r-Langerin+ dDCs showed inflammation comparable to that in WT mice. Furthermore, TSLP contributed to the upregulation of Langerin expression in BM-derived DCs and promoted the maturation of Langerin+ DCs. In summary, the present study demonstrated that the newly infiltrated inflammatory dermal Langerin+ DCs were essential for AD development and local TSLP production, and TSLP further promoted the production of BM-derived i-Langerin+ dDCs, which might maintain AD inflammation.